Pembentukan Karakter Mandiri Pada Anak Madrasah Ibtidaiyah Kelas 1 Dalam Perspektif Psikologi Islam - Lestari, Anggi Widya; Shanie, Arsan; Ramadhani, Kamalia Zuhriya; Nurrahma, Hanum Rahma; Muarikhah, Rizqi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to examine the development of independence character in first-grade Madrasah Ibtidaiyah (MI) students from the perspective of Islamic psychology. The elementary school years are a crucial phase in childrens character development, with independence as one of the fundamental life competencies. This research employs a qualitative descriptive approach conducted at MI Miftahul Akhlaqiyah Semarang, involving teachers and first-grade students as subjects. Data collection techniques include observation, interviews, and documentation. The findings indicate that the development of children's independence is influenced by several factors such as parenting style, teacher roles, modeling behavior, habituation, and peer environment. The implementation of independent character in the Islamic psychology perspective is carried out through consistent religious practices like congregational prayer, independent task assignments, and guidance that integrates spiritual values and personal responsibility. This study reveals that integrating Islamic values with psychological theories effectively fosters children's independence from an early age.